Labor Relations in Ontario Hospitals : A Question of Survival - Isbester, Fraser; Castle, Sandra (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
The authors examine the sources of the prevalent unrest among Ontario Hospital employees. As the specific causes of the present situation are outlined separately, their inter-relationships are to be borne in mind.